IMF Staff Papers, Volume 47, No. 2. (IMF Staff Papers; IMF Staff Papers ;, 2000)
This paper analyzes portfolio diversification, leverage, and financial contagion. It studies the extent to which basic principles of portfolio diversification explain 'contagious selling' of financial assets when there are purely local shocks. The paper demonstrates that the elementary portfolio theory offers key insights into 'contagion.' Most important, portfolio diversification and leverage are sufficient to explain why an investor will find it optimal to significantly reduce all risky asset positions when an adverse shock impacts just one asset.